Educational Management Model Based on Recognition of Prior Learning (RPL) for Lifelong Learning - Arfiani Yulianti Fiyul; Saurav Kumar (The International Journal of Education Management and Sociology, 2026)
This study aims to develop an educational management model based on Recognition of Prior Learning (RPL) to support lifelong learning. RPL is an approach that acknowledges knowledge, skills, and competencies acquired through formal, non-formal, and informal learning experiences. In the context of modern education, the implementation of RPL requires a systematic, integrated, and policy-driven management strategy to enhance accessibility, flexibility, and relevance of education for diverse learners. This research employs a qualitative approach with a research and development (R&D) design, involving needs analysis, model design, expert validation, and limited implementation trials. The findings reveal that the proposed educational management model consists of several key components, including strategic planning, competency assessment and validation systems, adaptive curriculum management, institutional capacity building, and continuous monitoring and evaluation. The model effectively improves the recognition of learners’ competencies, broadens access to education, and strengthens the linkage between education and the labor market. In conclusion, the RPL-based educational management model provides an innovative solution for developing an inclusive, flexible, and sustainable education system that supports lifelong learning in the modern era.